Pengaruh Literasi Keuangan, Pembelajaran Manajemen Keuangan, dan Uang Saku Terhadap Perilaku Menabung - Vivi Rikayanti Rikayanti; Agung Listiadi (Jurnal Pendidikan Akuntansi (JPAK), 2020)
Each individual has different characteristics and tendencies of saving behavior, both from internal and external factors. This study aims to determine and analyze the effect of financial literacy, learning financial management, and pocket money, simultaneously and partially affect the saving behavior of students of Accounting Education, Faculty of Economics, State University of Surabaya. The type of research used in this research is quantitative research. Sampling using purposive sampling technique with a total of 119 students. The data collection techniques used were questionnaires and tests. While the data analysis technique used is multiple linear regression analysis with the help of the SPSS version 22.0 program. Based on the results of the data analysis, it shows that: (1) financial literacy, learning financial management, and pocket money simultaneously have a significant effect on saving behavior, (2) financial literacy has a significant effect on saving behavior, (3) financial management learning has a significant effect on behavior saving, (4) pocket money has a significant effect on saving behavior.